1996
DOI: 10.1128/jb.178.2.377-384.1996
|View full text |Cite
|
Sign up to set email alerts
|

Identification of a region of genetic variability among Bacillus anthracis strains and related species

Abstract: The identification of a region of sequence variability among individual isolates of Bacillus anthracis as well as the two closely related species, Bacillus cereus and Bacillus mycoides, has made a sequence-based approach for the rapid differentiation among members of this group possible. We have identified this region of sequence divergence by comparison of arbitrarily primed (AP)-PCR ''fingerprints'' generated by an M13 bacteriophagederived primer and sequencing the respective forms of the only polymorphic fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
101
0
5

Year Published

1998
1998
2013
2013

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 115 publications
(107 citation statements)
references
References 34 publications
(23 reference statements)
1
101
0
5
Order By: Relevance
“…Other examples of bacterial VNTR loci occur inside ORFs (Andersen et al, 1996;Frknay et al, 1994). As expected all reported VNTR loci within bacterial coding regions have repeat sizes which are multiples of three.…”
Section: Vntr Loci In Coding Regionsmentioning
confidence: 99%
See 1 more Smart Citation
“…Other examples of bacterial VNTR loci occur inside ORFs (Andersen et al, 1996;Frknay et al, 1994). As expected all reported VNTR loci within bacterial coding regions have repeat sizes which are multiples of three.…”
Section: Vntr Loci In Coding Regionsmentioning
confidence: 99%
“…VNTR loci are also used for human forensic and paternity testing. Individual VNTR loci have been identified in bacteria (Andersen et al, 1996;Frknay et al, 1994;Frothingham, 1995;Goyal et al, 1994) but no systematic analysis has been reported. We undertook a systematic analysis of the variability of tandem repeat loci in the M .…”
Section: Introductionmentioning
confidence: 99%
“…Il B. anthracis possiede un DNA cromosomico e due plasmidi, pOX1 38 e pOX2 39 , sui quali si trovano i geni codificanti per i fattori di virulenza: la capsula 40 nel primo e la tossina dell'antrace 41 nel secondo, la quale è costituita da 3 subunità, letal factor (LF), edema factor (EF) e protective antigen (PA), ognuna codificata da un gene diverso 42 . Proprio sul B. anthracis furono sviluppati numerosi studi con lo scopo di individuarne i polimorfismi fino a quando, tra il 1996 e il 1997, due gruppi di scienziati arrivarono all'identificazione di 8 loci genici contenenti sequenze VNTR, che mostrarono un elevato grado di variabilità fra i diversi ceppi analizzati 43,44 . Per l'identificazione di questi loci furono sequenziati diversi frammenti di DNA attraverso la tecnica amplified fragment length polymorphism (AFLP) 45 , utilizzata anche per la determinazione delle relazioni filogenetiche del bacillo dell'antrace con gli altri bacilli della stessa famiglia (B. cereus e B. thuringiensis) 43,44,46 .…”
Section: Le Indagini DI Laboratoriounclassified
“…Proprio sul B. anthracis furono sviluppati numerosi studi con lo scopo di individuarne i polimorfismi fino a quando, tra il 1996 e il 1997, due gruppi di scienziati arrivarono all'identificazione di 8 loci genici contenenti sequenze VNTR, che mostrarono un elevato grado di variabilità fra i diversi ceppi analizzati 43,44 . Per l'identificazione di questi loci furono sequenziati diversi frammenti di DNA attraverso la tecnica amplified fragment length polymorphism (AFLP) 45 , utilizzata anche per la determinazione delle relazioni filogenetiche del bacillo dell'antrace con gli altri bacilli della stessa famiglia (B. cereus e B. thuringiensis) 43,44,46 . In particolare, 6 degli 8 loci polimorfici furono individuati sul DNA cromosomiale (CG3,vrrA,vrrB1,vrrB2,vrrC1,vrrC2) e altri due (pXO2-at e pXO1-aat) sui due plasmidi 43,44 .…”
Section: Le Indagini DI Laboratoriounclassified
“…[13][14][15] The first DNA signatures that were developed for anthrax PCR detection methods independently of plasmids occurrence were DNA fragments used to genotype B. anthracis. They include the vrrA marker, [26][27][28] the AC-390 gene, 29 and the SG-850/749 fragment. 30 These genetic markers provide limited specificity and require additional timeconsuming and labor-intensive post-PCR analysis steps.…”
Section: Literature Survey Of Pcr-based Detection Methodsmentioning
confidence: 99%